SAT0507 Implantable loop recorder can screen for incidental significant arrhythmias in scleroderma, with cardiac mri ecv and troponin biomarker, useful for risk stratification. (12th June 2018) - Dumitru, R.; Bissell, L.-A.; Abignano, G.; Erhayiem, B.; Fent, G.; Donica, H.; Burska, A.; Del Galdo, F.; Greenwood, J.; Plein, S.; Graham, L.; Buch, M.H.
Abstract : Background: Cardiac involvement and in particular conduction abnormalities represent a significant cause of morbidity and mortality in patients with systemic sclerosis (SSc). No studies assessed the value of implantable loop recorder (ILR) for early detection of arrhythmias in asymptomatic patients with SSc; or whether cardiac magnetic resonance (CMR) features associate with arrhythmias. Objectives: To assess the prevalence of conduction abnormalities over a 3 year period using an ILR (REVEAL) and evaluate relationship with disease phenotype, cardiac biomarkers and CMR in SSc patients. Methods: 20 patients(pts) with ACR/EULAR criteria for SSc, with no history of cardiovascular (CV) disease and ≤1 CV risk factor had 3T CMR with late gadolinium enhancement (LGE) and T1 mapping for ECV quantification. An ILR was then inserted, for 3 years follow-up. ILR data were downloaded every 3 months. Serum cardiac biomarkers were also measured at the initial visit. Results: 19 pts had available ILR data; 12 (63%) females, median (SD) age 53(, 12 6 (32%) diffuse SSc(dcSSc), 6 (32%) ACA+, 4 (21%) Scl70+, 8 (42%)history of interstitial lung disease (ILD) and 7 (36%) history of digital ulcers (DU). 14/19 had any ILR abnormalities, 8/14 significant arrhythmias: 1 complete heart block; 2 non-sustained ventricular tachycardia (NSVT), and 5 atrial arrhythmias (1 atrial flutter, 1 AF, 1 SVT, 1 AF and SVT and 1 AF followed by atrial flutter and SVT). Of these 8 pts, 4 had dcSSc, 2 Scl70+, 4 ACA+, 3 with ILD and 3 DU history. All 3 patients with severe arrhythmias (NSVT/CHB) were dcSSc, 2 Scl70+, 2 males. Management comprised 1 permanent pacemaker implantation, 3 antiarrhythmic treatment, 1 anticoagulation.15 pts had CMR. The 8 pts with significant arrhythmia appeared to have higher ECV, LV mass, and LVEF%(table 1). LGE was observed in 1(NSVT), of a total of 5/15 with LGE. HsTnI was considerably higher in those with significant arrhythmias[(mean diff.(95% CI)117 (-10, 245)].NTproBNP [(mean diff.(95% CI) 92 (-30, 214)] also appeared greater in those with significant arrhythmias. There was no difference in CK levels between the two groups. Conclusions: This pilot study demonstrates the ability of ILR to detect life-threatening arrhythmia in asymptomatic SSc pt. The data suggest CMR ECV(but not LGE) and cardiac biomarkers, in particular hsTnI (indicating subclinical myocardial injury) may be able to identify at risk pts that would benefit from ILR screening. Future studies can inform a risk model, and provide insight into the pathogenesis of SSc associated arrhythmias. Disclosure of Interest: None declared